2019
DOI: 10.3390/met9030360
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the Heating and Cooling Rates on the Dissolution and Precipitation Behavior of a Nickel-Based Single-Crystal Superalloy

Abstract: The effects of the heating rate before solution treatment, and the cooling rate after solution treatment on the morphological distribution and evolution of the precipitation phase of nickel-based single crystal superalloy were studied. The dissolution, precipitation, and growth of the precipitation phase and the matrix phase during heat treatment were analyzed by the means of high-power scanning electron microscopy. The results show that the morphology of the precipitated phase has nothing to do with the distr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Soucail et al [46,47] observed similar behavior for the dissolution rate of secondary γ' in Astroloy during heating. In particular, they found that the departure from equilibrium dissolution temperature was lower for smaller secondary γ' precipitates but increased with the heating rate in It has been reported [43][44][45] that changes in the heating rate modified the microstructure and the distribution of elements in the matrix resulting in changes in the chemical reaction temperatures and hence the DTA results. The results, reported in Table 3, quantify these changes for the examined samples in the present study and show that indeed the precipitation temperatures of γ , γ" and δ phases increased by increasing the heating rate because there was less time for elemental diffusion and chemical reactions for precipitation of each phase at higher rates.…”
Section: Low Heating Rate Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soucail et al [46,47] observed similar behavior for the dissolution rate of secondary γ' in Astroloy during heating. In particular, they found that the departure from equilibrium dissolution temperature was lower for smaller secondary γ' precipitates but increased with the heating rate in It has been reported [43][44][45] that changes in the heating rate modified the microstructure and the distribution of elements in the matrix resulting in changes in the chemical reaction temperatures and hence the DTA results. The results, reported in Table 3, quantify these changes for the examined samples in the present study and show that indeed the precipitation temperatures of γ , γ" and δ phases increased by increasing the heating rate because there was less time for elemental diffusion and chemical reactions for precipitation of each phase at higher rates.…”
Section: Low Heating Rate Testsmentioning
confidence: 99%
“…In this study, the focus was before liquation and melting because the melting temperature is principally independent of the heating rate. d 10 540 589 736 801 886 984 15 557 595 741 817 926 1008 25 560 614 754 831 962 1024 50 572 663 761 840 948 1035 80 596 678 776 860 965 1051 100 600 700 798 873 990 1057 It has been reported [43][44][45] that changes in the heating rate modified the microstructure and the distribution of elements in the matrix resulting in changes in the chemical reaction temperatures and hence the DTA results. The results, reported in Table 3, quantify these changes for the examined samples in the present study and show that indeed the precipitation temperatures of γ', γ" and δ phases increased by increasing the heating rate because there was less time for elemental diffusion and chemical reactions for precipitation of each phase at higher rates.…”
Section: Low Heating Rate Testsmentioning
confidence: 99%
“…While the lattice mismatch at room temperature was negative, its value was more negative at high-temperature. If the lattice mismatch degree was positive, its value decreased or became negative at high-temperature [ 23 ]. At the same time, the literature [ 27 ] also pointed out that the γ′ phase size distribution (PSD) was more consistent with the strain energy model in the early stage of heat treatment.…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…However, the huge differences in composition between coating and underlying substrate can lead to element interdiffusion during long-term high-temperature service, resulting in the segregation of insoluble elements such as Ta in the substrate and the precipitation of harmful topological close-packed 2 of 10 phase [15][16][17]. The main components of topological close-packed phases are W, Mo and Re, which are added in the superalloy for strengthening the comprehensive performance of superalloys at high temperature [18][19][20].…”
Section: Introductionmentioning
confidence: 99%